Heel Ulcer and Blood Flow: The Importance of the Angiosome Concept. (September 2013) - Faglia, Ezio; Clerici, Giacomo; Caminiti, Maurizio; Vincenzo, Curci; Cetta, Francesco
A young female diabetic patient is reported, who presented with a double foot lesion. She presented with a first metatarsal head exposure concomitant with a heel wet gangrene. Magnetic resonance demonstrated osteomyelitis of the rear portion of the calcaneus. Transmetatarsal amputation was performed and a wide debridement was required to remove all gangrenous tissue from the heel wound. The pedal artery was palpable; the posterior tibial pulse was present, but weak.Transcutaneous oximetry (TcPO2) at the dorsum of the foot was TcPO2 = 56 mmHg despite significant oedema. Nevertheless, TcPO2 on the perilesional area of the heel ulcer (TcPO2 = 24mmHg) was suggestive for critical chronic ischemia. At angiographic examination, anterior tibial and peroneal arteries were patent, but the posterior tibial artery that showed severe stenosis then percutaneous angioplasty (PTA) was performed. Just the day after PTA, values of TcPO2 at the perilesional area of the heel ulcer increased to 41 mmHg. Heel osteomyelitis was subsequently treated by partial calcanectomy. The patient was discharged after a 21-day hospital stay. In the treatment of heel ulcers, it is clinically useful to use the angiosomic concept. The majority of the blood supply to the heel is provided by the posterior tibial artery, and only to a small extent by the posterior branch of peroneal artery. If the decrease in blood flow to this region is not detected, and direct flow based on the angiosome concept is not obtained, the healing of a heel ulcer may be delayed or impaired.